When Democracies Retrench: A Case Study of Britain's Withdrawal from East of Suez - Zhang, Jerry (Tufts Archival Research Center, 2021)
A country is conducting a policy of retrenchment when it withdraws from its strategic commitments - its sustained efforts in achieving certain foreign policy objectives, often in the form of military presence or support for allies. Retrenchment often marks a dramatic turning point in a country’s foreign policy. The country gives up long-held strategic interests that only until recently have been deemed vital. However, study for such a vital state behavior is still lacking.This thesis hopes to contribute to the academic comprehension of retrenchment by focusing on retrenchment conducted by democratic states. Through an in-depth case study of Britain’s Cold War disengagement from East of Suez, it tries to understand what motivates a democratic state like Britain to undertake such policy. After analyzing policy debate and elite decision-making during that period, it argues that the presence of major policy failure, domestic institutional setups, and the presence of alternative policies are the most relevant factors that can explain a democratic retrenchment.; Advisor: Professor Michael Beckley